2017
DOI: 10.5217/ir.2017.15.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of preoperative 18F-fluorodeoxyglucose positron emission tomography/computed tomography for colorectal cancer: comparison with conventional computed tomography

Abstract: Background/Aims18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) has been used for preoperative staging of colorectal cancer (CRC). However, the diagnostic accuracy of FDG-PET/CT for detection of lymph node or distant metastasis and its prognostic role have not been well established. We therefore evaluated the diagnostic and prognostic value of FDG-PET/CT in comparison with conventional CT for CRC.MethodsWe investigated 220 patients who underwent preoperative FDG-PET/CT and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…However, a plethora of positive lymph nodes tend to be not detected abnormality because of low density, small diameter, regular form and so on (22). Indeed, the overall accuracy of evaluation of N-staging by contrast enhanced CT (ceCT) has been reported merely from 59% to 71% (23,24).…”
Section: N-staging: Involvement Of Regional Lymph Nodesmentioning
confidence: 99%
“…However, a plethora of positive lymph nodes tend to be not detected abnormality because of low density, small diameter, regular form and so on (22). Indeed, the overall accuracy of evaluation of N-staging by contrast enhanced CT (ceCT) has been reported merely from 59% to 71% (23,24).…”
Section: N-staging: Involvement Of Regional Lymph Nodesmentioning
confidence: 99%
“…For lymph node staging (Table 3B), the sensitivity was found to range from 44% to 73%, and the specificity ranged from 41% to 84%. [84][85][86][87][88][89][90] The accuracies of these studies were around 50%-60%. PET showed a relatively high specificity of 84%, but a sensitivity of only 44%.…”
Section: Lymph Node Stagingmentioning
confidence: 99%
“…In many tumor types, FDG-PET/CT showed a higher diagnostic accuracy than PET or CT alone for detecting tumor recurrence. Thus, it is more appropriate to use for patient selection for PM than other conventional imaging modalities (45)(46)(47). Recently, it was reported that dual-time point FDG-PET/CT could be useful for distinguishing primary and metastatic lung adenocarcinoma in patients with SPN (48).…”
Section: Radiological Examinationsmentioning
confidence: 99%